Biomolecular Recognition: ssDNA‐Functionalized Nanoceria: A Redox‐Active Aptaswitch for Biomolecular Recognition (Adv. Healthcare Mater. 7/2016). Issue 7 (April 2016) - Bülbül, Gonca; Hayat, Akhtar; Andreescu, Silvana
Abstract : The reversible assembly of single‐stranded DNA aptamers on redox‐active nanoceria particles, as presented by S. Andreescu and team on page 822, can be induced or resolved in response to a molecular target. Application of this mechanism for the design of a biomolecular aptaswitch for detection of ochratoxin A is demonstrated.